2005
DOI: 10.1097/01.tp.0000146844.65273.62
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Valganciclovir Administered as Preemptive Therapy for Cytomegalovirus Disease in Liver Transplant Recipients: Impact on Viral Load and Late-Onset Cytomegalovirus Disease

Abstract: Antigenemia-directed valganciclovir as preemptive therapy seems to be effective for the prevention of CMV disease in liver transplant recipients, including high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 20 publications
(21 reference statements)
6
78
0
Order By: Relevance
“…There is an urgent need for an effective oral treatment for pre-emptive CMV therapy, which would enable prevention and treatment of CMV in an outpatient setting leading to reduced patient burden and health-care cost. The finding of the therapeutic equivalence of oral valganciclovir and intravenous ganciclovir is a confirmation of previous reports with respect to pre-emptive [12][13][14]22 and prophylactic treatment 20 in solid organ transplant recipients.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…There is an urgent need for an effective oral treatment for pre-emptive CMV therapy, which would enable prevention and treatment of CMV in an outpatient setting leading to reduced patient burden and health-care cost. The finding of the therapeutic equivalence of oral valganciclovir and intravenous ganciclovir is a confirmation of previous reports with respect to pre-emptive [12][13][14]22 and prophylactic treatment 20 in solid organ transplant recipients.…”
Section: Discussionsupporting
confidence: 77%
“…[9][10][11] Recently, oral valganciclovir and intravenous ganciclovir were shown to have similar efficacy in pre-emptive CMV treatment in solid organ transplant recipients. [12][13][14] As a consequence, the prevention of CMV disease in high-risk renal, renal-pancreas and heart transplant patients was added as another indication to the original approval of valganciclovir for the treatment of CMV retinitis in AIDS patients. So far, no data are available on the efficacy of 900 mg valganciclovir twice daily as compared to intravenous 5 mg/kg ganciclovir twice daily in the pre-emptive therapy of CMV infection in stem cell transplant recipients and therefore valganciclovir is not licensed for use in allogeneic stem cell transplantation patients.…”
Section: Introductionmentioning
confidence: 99%
“…When conducted properly, preempti ve therapy, with the use of oral ganciclovir, IV ganciclovir, or val ganciclovir resulted in the reduction of CMV disease by about 70% [35,36,68] . Moreover, preemptive therapy is much less likely associated with late onset CMV disease (unlike in antiviral prophylaxis, as discussed below) [59,66] . Cur rently, valganciclovir is the most commonly used drug for preemptive therapy [64] , and in one noncontrolled study, it was demonstrated to be as effecti ve in terms of clinical and virologic response, as IV ganciclovir [59,66] .…”
Section: Preemptive Therapymentioning
confidence: 99%
“…Moreover, preemptive therapy is much less likely associated with late onset CMV disease (unlike in antiviral prophylaxis, as discussed below) [59,66] . Cur rently, valganciclovir is the most commonly used drug for preemptive therapy [64] , and in one noncontrolled study, it was demonstrated to be as effecti ve in terms of clinical and virologic response, as IV ganciclovir [59,66] . In addition, preempti ve therapy may be beneficial in reducing the in direct effects of CMV, although to a much lesser degree than anti viral prophylaxis.…”
Section: Preemptive Therapymentioning
confidence: 99%
See 1 more Smart Citation